The Interpretation of Freedom of Religion and Believe: How Do University Understand This to Society? - Rurin Sisilia Prasetyani; Shally Saniyya Novina (The Indonesian Journal of International Clinical Legal Education, 2020)
This paper is based on the condition of freedom of religion and belief and people's understanding of the meaning of freedom of religion and belief which is still wrong and ambiguous. In fact, as dignified beings, humans have a number of basic rights that must be protected, such as the right to life, the right to political rights, the right to assemble, as well as the right to religion and belief. Human rights values ​​teach that these basic human rights are protected and respected. Human rights teach the principle of equality and human freedom so that there can be no discrimination, exploitation and violence against humans in any form and also there should not be any restrictions and restrictions on basic human freedoms, including the right to freedom of religion. The Indonesian nation is a pluralistic nation. There are various kinds of ethnicity, race, religion, and ethnicity that cause diversity in Indonesia. Although the majority of Indonesian people are followers of Islam, however, in Indonesia there are also several other official religions recognized by the government, namely, Catholic Christians, Protestant Christians, Hindus, Buddhists, and Confucians. Therefore, every person has the right to freedom of religion or belief, that means no one may be subject to coercion that would interfere with his freedom to adhere to or embrace a religion or belief of his own choice.